Islamic Religious Education Learning Strategies in Improving Student’s Communication Skills - Hasibuan, Siti Syaidariah; Al Farabi, Mohammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to find out what learning strategies for Islamic Religious Education (PAI) teachers use in improving students' communication skills, the extent of the effectiveness of PAI learning strategies in improving students' communication skills, and how students respond to the use of PAI learning strategies used in improving students' communication skills. This research was conducted at Al-Hijrah IT Junior High School Deli Serdang, using a qualitative method with a descriptive design. The informants in this study consisted of 2 Islamic Religious Education teachers, school principals, curriculum representatives, and eight students. The data will be gathered through observations, interviews, and document studies. The data analysis used is data reduction, data presentation, and drawing of a conclusion. The results of this study show that the PAI learning strategy is used to improve students' communication skills by using a student-centered learning approach (Student Centered Learning) or a scientific approach, as well as presentation and discussion learning methods. The use of PAI learning strategies in improving students' communication skills from this study shows that the PAI learning strategies used are effective, which can be seen from students' responses to PAI learning strategies used in improving students' communication skills.